1992
DOI: 10.1084/jem.176.4.1227
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 8 (IL-8) selectively inhibits immunoglobulin E production induced by IL-4 in human B cells.

Abstract: SummaryThe effect of interleukin 8 (I1,8) on I1,4-induced immunoglobulin E (IgE) production was studied. I1,4 induced IgE and IgG4 production by tonsiUar mononuclear cells (MNC) without affecting IgM, IgG1, IgA, IgG2, or IgG3 production. IL-8 inhibited I1,4-induced IgE and IgG4 production, whereas it had no effect on IgM, IgG1, IgA, IgG2, and IgG3 production. The inhibitory effect by I1,8 was specific, since it was blocked by anti-I1,8 mAb, but not by control IgG1. Although interferon 3' (IFN-3') also inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 20 publications
1
52
0
1
Order By: Relevance
“…The higher in vivo increase in total and OVA-specific IgE in the IL-8r -/-OVA/OVA mice is consistent with the findings by two recent in vitro studies in which IL-8 was shown to selectively inhibit IL-4-induced IgE production in human B cells (43) and spontaneous IgE and IgG4 production in cultured B cells from atopic patients (42). The absence of the IL-8-mediated inhibition of IgE production in these IL-8r -/-mice most likely accounts for the significantly greater increase in serum IgE.…”
Section: Figuresupporting
confidence: 77%
See 1 more Smart Citation
“…The higher in vivo increase in total and OVA-specific IgE in the IL-8r -/-OVA/OVA mice is consistent with the findings by two recent in vitro studies in which IL-8 was shown to selectively inhibit IL-4-induced IgE production in human B cells (43) and spontaneous IgE and IgG4 production in cultured B cells from atopic patients (42). The absence of the IL-8-mediated inhibition of IgE production in these IL-8r -/-mice most likely accounts for the significantly greater increase in serum IgE.…”
Section: Figuresupporting
confidence: 77%
“…In view of the observation that IL-8 has been reported to inhibit IgE production in vitro (42,43), we hypothesized that in the absence of the IL-8 receptor homologue, IgE antibody titers would be increased. Indeed, significantly higher serum concentrations of total and OVA-specific IgE were observed in IL-8r -/-mice sensitized and challenged with aerosolized OVA than in the Wt OVA/OVA group.…”
mentioning
confidence: 99%
“…Immature B cells express HLA-DR [29], surface κ and λ light chains, CD9 [30], CD10 (which is lost before cells acquire sIgM, but re-expressed on later B cells, upon their activation [31]), CD19 [32]), CD20 (expressed beginning at the pre-B cell stage [32]), CD34 (which is lost upon maturation to the pre-B cell stage [33]), CD38 (expressed on immature and terminally differentiated B cells [34]), and CD40 (a pan-B marker, except not expressed on plasma cells [35]). Other markers we employed are expressed on mature and/or activated B cells: sIgD [36], CD11a [37], CD21 [38], CD22 (expressed shortly after CD19 in the cytoplasm of early B cells, then on the surface of mature B cells [39]), CD23 (activation antigen expressed on cells which simultaneously express both membrane IgM and IgD [40]), CD25 (the IL-2 receptor [41]), CD35 (the complement receptor 1 [42]), CD43 (expressed on most lymphocytes except resting B cells [43]), CD44 [44], CD45 [45], CD62L (L-selectin [46]), CD69 (an early activation marker [47]), and CD71 (transferrin receptor [48]). Finally, we used the monocyte-associated markers CD11b (the C3bi receptor) expressed on normal and malignant CD5 + B cells [26,49] and CD15 expressed on 25%-50% of the CD5 + B cells of patients with B-cell chronic lymphocytic leukemia and other chronic B cell disorders [49].…”
Section: Lymphoid Differentiation Antigens Expressed On Cd5 + B Cellsmentioning
confidence: 99%
“…Psoriasis is an immune-mediated inflammatory skin disorder and there is mounting evidence that levels of TNF-α, IL-6, IL-8 and IL-17, as crucial cytokines involved in psoriais's pathogenesis, are elevated in psoriasis [3]. Previous studies showed that IL-8 inhibited IL-4-induced IgE production and endogenous TNF-α and IL-6 are essential for IgE production in atopic patients [25,26]. In addition, IgE promotes the autocrine production of IL-6 in human lung mast cells [27].…”
Section: Discussionmentioning
confidence: 99%